Sense of coherence contributes to physical and mental health in general hospital patients in China - Li, Wentian; Leonhart, Rainer; Schäfert, Rainer; Zhao, Xudong; Zhang, Lan; Wei, Jing; Yang, Jianzhong; Wirsching, Michael; Larisch, Astrid; Fritzsche, Kurt (Psychology, health & medicine, 2015)
The sense of coherence (SOC) may explain why some people become ill under stress whereas others remain healthy. SOC is strongly related to perceived health, particularly mental health. Little is known about the physical and mental health statuses associated with SOC among general hospital outpatients in China. This multicentre cross-sectional study analysed 491 outpatients from four large Chinese general hospitals located in Beijing, Shanghai, Chengdu and Kunming.
Published online: 08 Sep 2014
Gesehen am 22.06.2020